2013
DOI: 10.1177/1947601913485415
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Lineage Kinase-c-Jun N-Terminal Kinase Axis: A Potential Therapeutic Target in Cancer

Abstract: Mixed lineage kinases (MLKs) are members of the mitogen-activated protein kinase kinase kinase (MAP3K) family and are reported to activate MAP kinase pathways. There have been at least 9 members of the MLK family identified to date, although the physiological functions of all the family members are yet unknown. However, MLKs in general have been implicated in neurodegenerative diseases, including Parkinson and Alzheimer diseases. Recent reports suggest that some of the MLK members could play a role in cancer v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Pre-clinical modeling of response to therapies for NF1 mutated melanoma also will need to account for co-occurring mutations. The NF1 mutant cohort harboring co-mutations in MAPK3K5/9 is of particular interest as they are upstream activators of the Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase pathways (Rana et al, 2013). The current study provides the reagents to further functionally characterize this interesting rare subtype of melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical modeling of response to therapies for NF1 mutated melanoma also will need to account for co-occurring mutations. The NF1 mutant cohort harboring co-mutations in MAPK3K5/9 is of particular interest as they are upstream activators of the Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase pathways (Rana et al, 2013). The current study provides the reagents to further functionally characterize this interesting rare subtype of melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The mitogen-activated protein kinase (MAPK) cascade is essential in the transduction of signals from the extracellular space to the nucleus (2). Four signaling pathways of the MAPK family have been identified in eukaryotic cells as follows: (i) The extracellular signal-regulated protein kinase (ERK); (ii) c-Jun N-terminal kinase (JNK)/stress-activated protein kinase (SAPK); (iii) ERK5/big MAP kinase (BMK1); and (iv) p38MAPK pathways (3). p38MAPK is a kinase induced by stress signals and can also be referred to as p38αMAPK (4).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we also reported recently that MLK3 kinase activity was down-regulated by IGF-1 and estrogen via activation of PI3K/AKT pathway (11). Specifically, the AKT activation, either by IGF-1 or estrogen directly, phosphorylates MLK3 on the Ser 674 site (13), and this phosphorylation suppresses the MLK3 kinase activity and prevents cancer cell death (13).…”
Section: Discussionmentioning
confidence: 92%
“…MLK3 is a member of a larger mixed lineage kinase (MLK) family, and the members are unique in the sense that their catalytic domains contain signature sequences of both serine/threonine and tyrosine kinases (11). Previous works by us and others have reported that MLK family members, including MLK3, activate c-Jun N-terminal kinase (JNK) (12).…”
mentioning
confidence: 99%